Avaliação de formulações cosméticas contendo bioaditivos antioxidantes derivados do LCC. - Santiago, Vívian Romero (2016)
The Brazilian companies together are responsible to produce annually 70,000 tons of almonds cashew, generating about 45 thousand tons of liquid cashew nut shell (CNSL) in the year. The CNSL is often discarded in Chestnut beneficiation process, but this fluid and its the main constituents (Cardanol and Cardol) are a natural source of phenolic compounds and unsaturated long chain. This feature gives some important properties for use as antioxidant activity. Assessing the main characteristics of this compound, the work was to study the activity of LCC constituents as active antioxidant potential for cosmetic products, for antioxidant efficacy in skin and repellent action. Formulations were prepared using cardanol, cardol saturated and unsaturated, in concentrations from 0.03 to 20% for bactericidal activity and more specifically from 0.03 to 0.1% antioxidant. Formulations BHT were prepared and used as a reference. By DPPH method it was possible to verify that all formulations showed higher antioxidant activity or similar to the formulations containing the BHT in all concentrations. In addition, these formulations were subjected to antimicrobial tests and were active against strains of Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus, indicating that in addition to antioxidant, these can be employed as antimicrobial active formulations. It has also produced a moisturizer repellent with LCC Natural, technical, and Cardol Cardanol comparing its activity to a commercial repellent N, N-dimethyl-meta-toluamide (DEET). In tests using mice, the product showed the percentage of repellency of 98% to 100% compared with the pure moisturizer. Furthermore, in studies with humans, it has been found that the Natural CNSL was repellency of 93.8%, followed by 92.4% cardol. These values ​​have proved to be equivalent to the percentage of commercial repellent DEET (93.6%). In addition to other activities, the cardanol was tested as a biological shield in pigskin, this asset was used to decrease free radicals in the skin with the submission to radiation UV. This was served to the skin with a proprietary delivery system favoring its solubility in aqueous vehicles and their permeation into the skin. It was shown to reduce the formation of radicals lives in the presence of this antioxidant. Thus, the results presented here will contribute to sustainable development and origin of natural and effective raw materials. However, many studies are still necessary in order to add value to a substrate that has a lot of potential but that is little explored.